Does Storytelling Reduce Stigma? A Meta-Analytic View of Narrative Persuasion on Stigma Reduction - Zhuang, Jie; Guidry, Ashley (Basic and applied social psychology, 2022)
Stigmatization of one or more discredited attributes has a profoundly negative social impact on stigmatized individuals. Researchers have applied narratives as a persuasion device to reduce stigma. However, the overall effect of narratives on stigma is yet known. This research synthesized and quantified the effect of narratives in reducing stigma and identifies moderating factors. Forty-six effect sizes were extracted from 40 articles investigating the effect of narratives on stigmatization in various stigmatized conditions. A small effect of narratives on reducing stigma was yielded, which indicated that narratives were effective in reducing stigma. Narratives constructed with the first-person point of view were to be superior in reducing stigma. Theoretical and practical implications are discussed.